The Role Of E-Learning In Producing Independent Students With Critical Thinking (International Journal of Engineering and Computer Science, 2015)
This research provides a thorough background on E-learning and how it has come about. The research focuses on the important role of E-learning in a time when life is saturated with technology. This paper also explains how E-learning can be an effective way of learning. The research attempts to take UHD students from both colleges of computer science and Languages as samples. The paper deals with fundamental achievements one can gain through E-learning. Life is a non-stop process towards technology and E-government with all different parts. In such a livelihood, how can E-learning help improve a nation and help advance a country. This paper also attempts to understand the role of E-learning in advancing KRI. This paper answers the following questions this research provides a thorough background on E-learning and how it has come about. The research focuses on the important role of E-learning in a time when life is saturated with technology. This paper also explains how E-learning can be an effective way of learning. The research attempts to take UHD students from both colleges of computer science and Languages as samples. The paper deals with fundamental achievements one can gain through E-learning. Life is a non-stop process towards technology and E-government with all different parts. In such a livelihood, how can E-learning help improve a nation and help advance a country. This paper also attempts to understand the role of E-learning in advancing KRI.